Analisis Perubahan Konsumsi E-commerce Di Indonesia Selama Pandemi Covid-19 - Siti Nur Faizah; Jalu Aji Prakoso (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2021)
Writing this study aims to determine increased access to e-commerce, increased spending in online shopping on e-commerce sites, and effect variable trust, ease, hedonic motivation, price, promotion, shopping experience, and product quality on consumer behavior in online shopping during pandemic Covid-19. The data used are primary data be in the form of a questionnaire with sampling technique random sampling—Metode of analysis data in this study their descriptive analysis and multiple linear regression. The analysis result shows increasing access to e-commerce sites during pandemic Covid-19 and increasing spending in online shopping through e-commerce sites during pandemic Covid-19. Analysis result of multiple linear regression shows that variable ease, price, promotion, shopping experience, and product quality significantly affect consumer behavior during the pandemic Covid-19. At the same time, trust and hedonic motivation does not have a significant effect. E-commerce continues to develop features to make it easier for consumers and ensure transaction security. That considerable effect on consumer behavior during the pandemic Covid-19 and product quality variable significantly affect consumer behavior during the pandemic Covid-19. Results of the analysis can be concluded that during pandemic Covid-19, there is increasing access to e-commerce sites and increasing spending in online shopping through e-commerce sites.